Global spatial organisation of air transport: The definition of functional airline regions. Issue 1 (18th July 2019) - Halás, Marián; Kraft, Stanislav; Klapka, Pavel
Abstract : This paper deals with the issue of functional regionalisation on the global level and uses information on air transport movements as the regionalisation criterion. The analysis is based on analogies regarding the use of traditional methods, scale, and character of input information (flows) by which functional regions are usually defined. The paper tries to verify whether these analogies are viable and whether the approach can be used to assess the spatial organisation of air transport on the global level. In order to do so, the paper discusses some aspects of the development of air transport and then defines functional airline regions and their prominent cores (i.e., hub airports). The regionalisation algorithm uses a database containing more than 48, 000 routes and connecting almost 1, 000 airports. The results are discussed in relation to issues concerning the spatial concentration of world air transport, the spatial patterns of global functional airline regions, and the classification of world airline hubs. Abstract : This paper deals with the issue of functional regionalisation on the global level and uses information on air transport movements as the regionalisation criterion. The regionalization algorithm uses a database containing more than 48, 000 routes and connecting almost 1, 000 airports. The results are discussed in relation to issues concerning the spatial concentration of world air transport, the spatial patterns of global functional airline regions, and the classification of world airline hubs.